Cytokine Storm of COVID-19 and Its Impact on Patients with and without Chronic Liver Disease - Premkumar, Madhumita (J Clin Transl Hepatol, 2021)
The coronavirus pandemic has resulted in increased rates of hepatic decompensation, morbidity and mortality in patients suffering from existing liver disease, and deranged liver biochemistries in those without liver disease. In patients with cirrhosis with coronavirus disease 2019 (COVID-19), new onset organ failures manifesting as acute-on-chronic liver failure have also been reported. The severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) also directly binds to enterocytes and cholangiocytes via the angiotensin converting enzyme receptor 2, although the lung remains the portal of entry. Superadded with the COVID-19 related bystander hepatitis, a systemic inflammatory response is noted due to unregulated macrophage activation syndrome and cytokine storm. However, the exact definition and diagnostic criteria of the ‘cytokine storm’ in COVID-19 are yet unclear. In addition, inflammatory markers like C-reactive protein, ferritin, D-dimer and procalcitonin are frequently elevated. This in turn leads to disease progression, activation of the coagulation cascade, vascular microthrombi and immune-mediated injury in different organ systems. Deranged liver chemistries are also noted due to the cytokine storm, and synergistic hypoxic or ischemic liver injury, drug-induced liver injury, and use of hepatotoxic antiviral agents all contribute to deranged liver chemistry. Control of an unregulated cytokine storm at an early stage may avert disease morbidity and mortality. Several immunomodulator drugs and repurposed immunosuppressive agents have been used in COVID-19 with varying degrees of success.